Validating UTF‐8 in less than one instruction per byte - Keiser, John; Lemire, Daniel (Software, practice & experience, 2021)
The majority of text is stored in UTF‐8, which must be validated on ingestion. We present the lookupalgorithm, which outperforms UTF‐8 validation routines used in many libraries and languages by more than 10 times using commonly available single‐instruction‐multiple‐data instructions. To ensure reproducibility, our work is freely available as open source software.